Assessing the determinants of domestic water conservation intention - Mohd Nazri, Sheik Muhammad Fareis; Raja Ahmad, Raja Adzrin; Azmi, Nurul Azlin; Md Yatim, Nurul Huda; Samsudin, Syamsyul (GADING Journal for the Social Sciences, 2023)
Malaysia has an enormous amount of water resources. Over the years, its development has served as the cornerstone of the nation’s socioeconomic growth. However, recent years have seen an increase in the demand for water that exceeds the availability of water resources in the country. Malaysia’s average daily water consumption is greater than the United Nation’s benchmark for water usage of 165 litres per capita per day. Therefore, the aim of this study is to discover the drivers that lead to high domestic water consumption in Malaysia compared to the recommended daily water consumption as set by the United Nations. This study also aimed to determine which attitudinal predictors have a significant relationship with the water conservation intention by employing the theory of planned behaviour in order to determine Malaysians’ consumption behaviour towards water usage. This study applied quantitative methodology and the data collected were analysed using SPSS software. The results indicate that water conservation attitude, subjective norms and perceived behavioural control had a significant and positive relationship with water conservation intention. The result of this study, thus, can contribute towards efforts by relevant authorities and parties to maintain the balance of water supply and demand.